(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article is devoted to the study of the problem of the formation of scientific thinking among graduate students in psychological-pedagogical field of training. The theoretical review analyzes the research of foreign and Russian authors from various points of view covering this problem. The d-efinition of scientific thinking is given as a type of intellectual activity conditioned by a specific motivation of a person and representing the process and result of solving a scientific problem, which consists in building an algorithm for its solution. The methods and conditions contributing to the formation of scientific thinking of graduate students are considered. The results of an empirical study of the masters’ understanding of the specifics of scientific thinking and attitudes towards it are presented.